Molecular diagnostic methods for rapid diagnosis of central nervous system infections - Venkatareddy, Mallikarjuna Pedduru; Upadhya, Dinesh; Yegneswaran, Prakash Peralam; Varghese, Aneena; Pahadasingh, Suryadipali; Prabhu, Arvind N.; Saravu, Kavitha; Shettigar, Kavitha S. (Frontiers in Medical Technology, 2025)
Central nervous system infections (CNSI) are serious life-threatening conditions caused by bacteria, viruses, fungi, and parasites and lead to high morbidity and mortality worldwide. Therefore, rapid identification of causative organisms and appropriate treatment are important. The traditional identification methods are time-consuming and lack sensitivity and specificity. Although culture method is gold standard for CNSI, it is time-consuming and microbiology reporting requires several days. Multiplex PCR assays can detect multiple pathogens simultaneously in clinical samples and overcome the limitations of conventional identification techniques. Despite the availability of several commercial molecular-based platforms for the detection of pathogens causing CNSI, there are still limitations in terms of cost, false positive results, and false negative results, which are limited to targeted pathogens in the panel. Moreover, validation of many commercially available and in-house laboratory-developed molecular assays is still lacking. In addition, molecular diagnostic tests need to be used in correlation with the clinical context to ensure better diagnosis and management of infections.